Ektobakteri Pada Ikan Nila (Oreocromis niloticus) Di Desa Lihung Kecamatan Karang Intan Kabupaten Banjar Propinsi Kalimantan Selatan - Anny Rimalia; Ramadhana, Sri (Fakultas Pertanian UVAYA Banjarmasin, 2023)
Intensive cultivation often risks the emergence of disease, this is because in intensive cultivation tilapia are kept with high stocking densities and intensive use of feed, which causes a decrease in water quality which in turn can trigger the emergence of disease. Fish diseases arise due to an imbalance between fish as gills of pathogens/microorganisms that carry disease, and the environment. The fish's defense system can be disrupted due to environmental changes and the development of pathogens in a cultivation container. This research aims to find out whether there are ectobacteria in tilapia fish in fish farming ponds in Lihung Village. The results of the research will make it easier to provide information about sick fish and how to deal with disease in the environment of fish cultivating ponds that are attacked by ectobacteria. The research was carried out for 10 days, 4–14 March 2023 at the KIPM Banjarmasin Laboratory, starting from taking test fish samples, necropsy, microscopic examination, as well as the types of ectobacteria found in tilapia seeds taken from fish farming ponds. Necropsy activities are carried out by weighing the weight of the test fish, checking the completeness of the fish's body organs and checking the body of the fish that will be observed. All samples of the test fish are weighed according to the required standard of at least 10 grams with a fish body weight of 50 grams, for completeness. body organs of all test fish samples are complete. From the sample results, it was found that there were 2 bacteria that attacked Tilapia fish in Lihung Village, namely Aeromonas sp. and Proteus sp bacteria